eCM 2019
DOI: 10.22203/ecm.v038a17
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone: chondroprotective corticosteroid or catabolic killer?

Abstract: While glucocorticoids have been used for over 50 years to treat rheumatoid and osteoarthritis pain, the prescription of glucocorticoids remains controversial because of potentially harmful side effects at the molecular, cellular and tissue levels. One member of the glucocorticoid family, dexamethasone (DEX) has recently been demonstrated to rescue cartilage matrix loss and chondrocyte viability in animal studies and cartilage explant models of tissue injury and post-traumatic osteoarthritis, suggesting the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 97 publications
2
40
0
Order By: Relevance
“…Low concentrations of Dex were able to protect cartilage explants from TNF- α and high dosage suppressed GAG content loss [ 29 ]. Black et al suggested in IL-1 α -stimulated bovine cartilage explants that Dex treatment largely inhibited transcriptions of IL-6, MMP-3, and MMP-13 [ 30 ]. Therefore, in the present study, we chose Dex as our positive medicine to dampen RA in vitro experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of Dex were able to protect cartilage explants from TNF- α and high dosage suppressed GAG content loss [ 29 ]. Black et al suggested in IL-1 α -stimulated bovine cartilage explants that Dex treatment largely inhibited transcriptions of IL-6, MMP-3, and MMP-13 [ 30 ]. Therefore, in the present study, we chose Dex as our positive medicine to dampen RA in vitro experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from other studies, degenerative changes in the cartilage of the knee joints of adult rats are accompanied by ultrastructural changes; that is, a decrease in the amount of rough endoplasmic reticulum and Golgi apparatus, an increase in glycogen content after 5 weeks of DXM administration [34], an increase in cell mortality rate, a decrease in the length of endoplasmic reticulum, a decrease in the number of Golgi apparatus, and a decrease in mitochondrial pool and size after 3 weeks of DXM administration [35]. Taken together, the results on the effects of DXM on the articular cartilage in healthy animals are controversial; DXM has been shown to affect cartilage and chondrocytes depending on the treatment duration [36].…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms of the corticosteroids' effects may be associated with changes in GAGs. The GAG content seems to be increased after DXM injection by reducing the activity of extracellular degradation enzymes [36]. However, according to another work, 9-week administration of other corticosteroid drug cortisone to adult rabbits led to a gradual decrease in the component of GAG-the hexosamine concentration content in articular cartilage [38] and a 55% decrease in GAG content in epiphyseal and articular cartilages of pony foals knee joint after 3 months of treatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, dexamethasone is the drug with fewer adverse side effects and wider clinical application. Thus, dexamethasone has been considered the front line drug to inhibit OA-induced inflammation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%